Ledipasvir–sofosbuvir for 6 weeks to treat acute hepatitis C virus genotype 1 or 4 infection in patients with HIV coinfection: an open-label, single-arm trial. (May 2017) - Rockstroh, Jürgen K; Bhagani, Sanjay; Hyland, Robert H; Yun, Chohee; Dvory-Sobol, Hadas; Zheng, Wei; Brainard, Diana M; Ingiliz, Patrick; Lutz, Thomas; Boesecke, Christoph; Nelson, Mark
Summary: Background: The latest European Association for the Study of the Liver (EASL) guidelines now recommend that patients with acute hepatitis C virus (HCV) infection should be treated with a combination of sofosbuvir and an NS5A inhibitor for 8 weeks. However, the ideal duration of treatment with interferon-free regimens, particularly in HIV-coinfected individuals, remains unknown. We assessed the efficacy and safety of 6 weeks of ledipasvir–sofosbuvir for acute genotype 1 or 4 HCV in HIV-1-coinfected patients. Methods: This open-label, single-arm trial, done in Germany and the UK, included patients with acute HCV genotype 1 or 4 and HIV-1. At screening, patients were either receiving HIV antiretrovirals and had HIV RNA less than 200 copies per mL, or not receiving antiretrovirals and had a CD4 T-cell count of greater than 500 cells per μL. All patients received ledipasvir–sofosbuvir once daily for 6 weeks. The primary efficacy endpoint was the proportion of patients with sustained virological response 12 weeks after the end of treatment (SVR12). This study is registered withClinicalTrials.gov, numberNCT02457611 . Findings: Between June 11, 2015, and Jan 8, 2016, we enrolled and treated 26 patients. All (100%) were men, 24 (92%) were white, and 25 (96%) were receiving antiretroviral treatment. 19 (73%) had genotype 1a and seven (27%) had genotype 4 HCV. Overall, 20 (77%; 95% CI 56–91) of 26 patients achieved SVR12: 15 (79%) of 19 with genotype 1a, and five (71%) of seven with genotype 4. Of six patients not achieving SVR12, three relapsed, two achieved sustained virological response 4 weeks after the end of treatment but were lost to follow-up, and one was reinfected. The most common adverse events were fatigue (seven participants [27%]), nasopharyngitis (seven [27%]), and headache (six [23%]). No patient discontinued or interrupted therapy due to adverse events. No HIV rebound occurred during the study. Interpretation: The rate of cure with a fixed-dose combination of ledipasvir–sofosbuvir for patients with acute genotype 1 or 4 HCV infection and HIV-1 coinfection is similar to historic rates with interferon-based treatment, but with shorter treatment duration and more favourable safety outcomes. Funding: Gilead Sciences.